Physical, physicochemical and centesimal characterization of jatobá-do-cerrado (Hymenaea stigonocarpa Mart.) - Silva, Edilene Ferreira da; Batista, Elisabeth Mariano; Almeida, Érica Jamily do Nascimento; Lemos, Lúcia Mara dos Reis; Barcelos, Samuel Carneiro de; Souza, Pahlevi Augusto de (Revista Verde de Agroecologia e Desenvolvimento Sustentável, 2020)
Among the native species of the Cerrado is the jatobá, a tree legume that has a fruit, in which its flour pulp has strong potential for enriching preparations. The objective was to evaluate the physical characteristics of the fruit of jatobá-do-cerrado (Hymenaea stigonocarpa Mart.), And the physical-chemical characteristics and centesimal composition in the pulp, seed and skin of the fruit. The jatobá pulp was homogenized and called Pulp Flour (FP). The seeds and husks of the jatoba were macerated and reduced and then crushed in an industrial blender, obtaining the flours called Seed Flour (FS) and Shell Flour (FC). The biometric variables of the seeds and fruits of the jatoba were evaluated. The results obtained validate the possibility of FP and FS being used as an ingredient in the protein enrichment of foods, due to the significant amount of this component. In addition, FP and FC showed potential for application in foods that contain low fiber content, as they showed expressive results for crude fiber (17,82 and 38,55%, respectively). All the analyzed parts of the fruit obtained considerable sources of nutrients, enabling their use in the preparation of new food products, as they presented high levels of proteins, carbohydrates and fibers.